O-GlcNAc modification regulates autophagy and apoptosis in endometriosis - Xiaohan Jin; Yali Feng; Lei Xu; Jing Li; Linping Fan; Jinge Li; Runyuan Liu; Qing Yang; Ying Kong; Yuhong Shang (Functional & Integrative Genomics, 2026)

Study on alkyl sulfonate enhanced sulfidization-amine flotation of fine-grained smithsonite based on foam stability regulation - Shuangrong Deng; Ximei Luo; Linping Qi; Xingchen Leng; Jianing Lv; Yuqiao Feng; Yunfan Wang (Minerals Engineering, 2026)

Continuous hollow spiral microfibers with embedded microchannels for synergistically enhanced atmospheric water harvesting and storage - Yuqiu Guo; Yalan Liu; Chuanjiyue Zhou; Ze Lv; Qianqian Wang; Wei Wu; Bolin Ji; Linping Zhang; Xueling Feng; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2026)

Electrochemical degradation of dibutyl phthalate in simulated printing and dyeing textile wastewater using cerium and stearic acid-modified Ti/TiO2-NTs/PbO2-Ce-SA electrode - Dexiang Liao; Fan Yang; Linping Tang; Fan Wu; Fang Yin; Lisu Chen; Daolun Feng (Journal of Water Process Engineering, 2026)

Kalirin as a key mediator of aluminum-induced cognitive dysfunction and neurotoxicity: Integrated evidence from occupational and cellular studies - Le Zhao; Jinzhu Yin; Mingxing Li; Yujun Ma; Shihui Guo; Guangsen Feng; Jing Song; Linping Wang; Huifang Zhang; Baolong Pan; Xiaoting Lu (Chemico-Biological Interactions, 2026)

Diaporthe cercidis causing leaf blight on Magnolia grandiflora in China - Shaohua Huang; Jia Cao; Linping Zhang; Jie Feng (Crop Protection, 2025)

A moderated mediation of tau phosphorylated sites in the association between occupational aluminum exposure and cognitive function - Yujun Ma; Guangsen Feng; Shihui Guo; Jing Song; Linping Wang; Huifang Zhang; Jinzhu Yin; Xiaoting Lu (NeuroToxicology, 2025)

A systematic review of non-dietary human risks of neonicotinoids in China: environmental concentrations, human exposure and risk assessment - Liping Sun; Zhixuan Wu; Linping Cao; Guohua Zhu; Xiawen Qiu; Huajun Feng; Haifeng Zeng; Xinyan Zhou (Environmental Pollution, 2025)

Janus-structured thermally conductive radiative cooler for electronic devices heat dissipation - Xiuyan Yan; Jinru Liu; Linping Zhang; Yi Zhong; Bolin Ji; Wei Wu; Bijia Wang; Xueling Feng; Liduo Rong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

First report of Michelia maudiae leaf blight caused by Colletotrichum siamense in China - Shaohua Huang; Jia Cao; Yuxuan Huang; Qianying Luo; Jiayu Luo; Qian Li; Jiahui Huang; Ningwei Mao; Pengmin Fan; Jie Feng; Linping Zhang (Crop Protection, 2025)

Occupational aluminum exposure in northern China’s large-scale plants: Unveiling dual-pathway mediation of fasting blood glucose and systolic blood pressure in cognitive impairment among workers - Xin Guo; Qiang Yang; Fangyu Gao; Baolong Pan; Feng Gao; Jingsi Zhang; Shanshan Wang; Xiaoting Lu; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu (NeuroToxicology, 2025)

Optimization of Phaeodactylum tricornutum cultivation for enhancing mariculture wastewater treatment and high value product recovery using Box–Behnken design - Feng You; Yiwei Fan; Linping Tang; Xiangrong Liu; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Process Safety and Environmental Protection, 2025)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

Hybrid chiral nanocellulose-cyanidin composite with pH and humidity response for visual inspection and real-time tracking of shrimp quality and freshness - Yingxuan Feng; Jian Lin; Xinjie Chen; Hao Chai; Linping Tian; Jiayi Zhang; Qingfeng Sun; Yushan Yang; Yingying Li (Food Chemistry, 2024)

Research on Time-Cooperative Guidance with Evasive Maneuver for Multiple Underwater Intelligent Vehicles - Zuoe Fan; Hao Ding; Linping Feng; Bochen Li; Lei Song (Journal of Marine Science and Engineering, 2024)
In order to achieve the precise attack of multiple underwater intelligent vehicles (UIVs) on the same target ship at a fixed impact time, and to improve the penetration capability of the UIVs themselves, this study investigated the guidance law for the time-cooperative guidance of UIVs with maneuvering evasion. The evasive maneuver of the UIV increases the line-of-sight angle between the UIV and the target, which decreases the guidance precision of the UIV. A segmented control strategy is proposed to solve the problem of decreasing guidance precision caused by evading maneuvers, which is also the main contribution of this paper. This control strategy is dividing the guidance trajectory into two segments. The first segment allows for intelligent underwater vehicles to make evasion maneuvers and penetrate the defense, while the second segment controls the terminal time and achieves precision strike. Different desired target-vehicle distances are designed for each segment, unifying the impact time control issue and evasion maneuver problem into the pursuit of desired target-vehicle distances. Finally, based on feedback linearization control theory, a time-cooperative guidance law with evasion maneuver capability is proposed. Simulation results validate the effectiveness of the proposed method in attacking-moving targets.

The responding mechanism of indigenous bacteria in municipal wastewater inoculated with different concentrations of exogenous microalgae - Xinyue Yang; Linping Liu; Xudong Liu; Shulian Xie; Jia Feng; Junping Lv (Journal of Environmental Management, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)